Analysis of the Needs of Game-based Learning Media for Learning Javanese in Elementary Schools - Alvin Mujahid; Munawir Yusuf; Abdul Haris Setiawan (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
At present there are many students who cannot fulfill the rules in communi-cating in Javanese according to applicable norms. Therefore, this study aimed to identify the needs of game-based learning media that are able to fa-cilitate students learning Javanese both in theory and practice. The research method is quantitative research, with a survey type. The collection instru-ment used was a questionnaire. The sample involved in this research consist-ed of 40 elementary school students. Responses from the questionnaire were then analyzed descriptively with percentages. The results of this research in-dicate that students have fairly good skills in operating smartphones, on their cellphones they also have various games installed that they often play with a duration of about >60 minutes to play a game without feeling bored, some of them then provide suggestions regarding the components that need to be in an educational game, namely pictures of material and questions accompa-nied by discussion. Through this research, it was identified that game-based learning media has the potential and opportunities to be applied to Javanese language learning so that students are skilled and understand the learning ma-terial.